Early childhood education professionals knowledge about foreign body airway obstruction (ovace) in children: an integrative review - Lima, Larissa Santos de (2024)
Introduction: In Brazil, in 2021, 2,339 deaths were recorded in the age group from 0 to 5 years of age due to accidental causes, among the causes, Foreign Body Airway Obstruction (OVACE) is in third place in the ranking. Objective: Identify existing knowledge and presence of training on OVACE for early childhood education teachers. Method: This is an integrative literature review. The PICO strategy was used to establish the following guiding question: “do early childhood education professionals receive training and have sufficient knowledge to act in OVACE situations?”. The study included articles published in the last 5 years (2019 to 2022), in Portuguese and English. The databases used to search for scientific articles were: Pubmed and Virtual Health Library (VHL). Results: 172 studies were identified and, after excluding the 11 duplicates, 161 remained for analysis: 133 in the National Library of Medicine (Pubmed) and 28 in the Virtual Health Library (VHL). After applying the inclusion and exclusion criteria, 5 articles were included in the sample. The lack of preparation of educators in relation to identification and intervention measures in cases of OVACE was evident, as well as deficiencies related to training.